Matematyka

Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska

Wydawnictwo:Nowa Era

Rok wydania:2015

Usuń niewymierność z mianownika 4.43 gwiazdek na podstawie 7 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

Usuń niewymierność z mianownika

54
 Zadanie
55
 Zadanie
56
 Zadanie

57
 Zadanie

`a)\ 1/(2-sqrt3)=1/(2-sqrt3)*(2+sqrt3)/(2+sqrt3)=(2+sqrt3)/(2^2-sqrt3^2)=(2+sqrt3)/(4-3)=(2+sqrt3)/1=2+sqrt3` 

`b)\ 4/(sqrt6-2)=4/(sqrt6-2)*(sqrt6+2)/(sqrt6+2)=(4(sqrt6+2))/(sqrt6^2-2^2)=(4(sqrt6+2))/(6-4)=(4(sqrt6+2))/2=2(sqrt6+2)` 

`c)\ 2/(3+sqrt5)=2/(3+sqrt5)*(3-sqrt5)/(3-sqrt5)=(2(3-sqrt5))/((3+sqrt5)(3-sqrt5))=(2(3-sqrt5))/(3^2-sqrt5^2)=(2(3-sqrt5))/(9-5)=(2(3-sqrt5))/4=(3-sqrt5)/2` 

`d)\ (2sqrt3)/(sqrt3+2)=(2sqrt3)/(sqrt3+2)*(sqrt3-2)/(sqrt3-2)=(2sqrt3(sqrt3-2))/((sqrt3+2)(sqrt3-2))=(2sqrt3(sqrt3-2))/(sqrt3^2-2^2)=(2sqrt3(sqrt3-2))/(3-4)=` 

`\ \ \ =(2sqrt3(sqrt3-2))/(-1)=-2sqrt3(sqrt3-2)=-2*3+4sqrt3=-6+4sqrt3`